Efektifitas Iklan Online Berbasis Media Sosial Antara Instagram dan Tiktok Studi Kasus: Video Promosi “Lumina Luminalis” dari Brand Evolvie Studios - Sundari, Cisilia Sundari; Saputra, Nikolaus Rama; Yusnanto, Tri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effectiveness of social media–based online advertising by comparing Instagram and TikTok as promotional platforms. The research uses the promotional video “Lumina Luminalis” from the local fashion brand Evolvie Studios as a case study. A qualitative descriptive approach was employed using a case study method. Primary data were obtained from content insight analytics on Instagram and TikTok, while secondary data were collected through in-depth interviews with five informants to support data triangulation. The analysis is grounded in Social Media Engagement Theory and Media Dependency Theory to assess each platform’s role in increasing consumer engagement and brand awareness. The results indicate that Instagram is more effective than TikTok in promoting the “Lumina Luminalis” video content. Instagram achieved higher reach, interaction rates, content replay, and profile visits, reflecting stronger user engagement and more effective brand exposure. Conversely, TikTok showed lower average watch duration, weaker audience retention, and limited interaction, despite its ability to reach new users through the For You Page algorithm. These findings suggest that Instagram’s visual features, interactive tools, platform credibility, and user experience contribute more significantly to sustained engagement and brand awareness.This study provides theoretical contributions to digital advertising and social media research by offering comparative insights into platform effectiveness using identical promotional content. Practically, the findings serve as a reference for marketers and brand owners in determining appropriate social media platforms for effective promotional strategies.